ETHYLENE CARBONATE ADSORPTION AND DECOMPOSITION STUDY ON BINARY METAL OXIDE-BASED CATHODE COATING IN LITHIUM-ION BATTERY USING DENSITY FUNCTIONAL THEORY - Rendy, Bernardus
Lithium-ion batteries are commonly used as energy storage for daily life purposes. However, these batteries are far from perfect. They experience capacity degradation over cycles of usage. One source of its capacity degradation is the side reaction on the cathode, which reduces the number of cathode active materials. The side reaction is restrained by solid permeable interphase (SPI) that naturally occurs through organic electrolyte components decomposition. Although, this natural SPI is not an optimized solution due to uncontrolled growth. In controlling the growth of SPI, binary metal oxide cathode coatings are widely used. This type of coating can alter SPI components and restrain side reactions, hence increasing the durability of the cathode. Previous experiments and computations have shown that coatings control the SPI by slowing down the electrolyte decomposition. Nevertheless, further probing to understand the decomposition reaction mechanism is quite challenging due to the complex nature of the solid-liquid interface. Therefore, computational methods are used in this study. In this undergraduate thesis, density functional theory calculations are used to semi-quantitatively study ethylene carbonate, as one of the organic electrolyte components, initial decomposition reaction rates on Al2O3, MgO, TiO2, and ZrO2 surfaces from adsorbed states. The calculations are implemented on QUANTUM ESPRESSO software. Initial decomposition energies are used as reaction rate parameters, as shown by the 2019 undergraduate thesis. Additionally, the effects of oxygen vacancy on initial decomposition energy are discussed. Herein, all initial decomposition energy trends on stoichiometric surfaces and surfaces with oxygen monovacancy are discussed. After that, the verification of initial decomposition energy as a reaction rate parameter is shown through the comparison between the initial decomposition energies of the coatings and bare cathodes. Next, the relations between average initial decomposition energies and coatings’ durabilities are shown. Finally, the effects of oxygen vacancy on decomposition reaction rates are discussed as insights in designing more efficient coatings.